Different Electroclinical Manifestations of the Epilepsy Associated with Hamartomas Connecting to the Middle or Posterior Hypothalamus - Leal, A (2016)
PURPOSE: The epilepsy associated with hypothalamic hamartomas (HHs) has typical clinical, electrophysiologic, and behavioral manifestations refractory to drug therapy and with unfavorable evolution. It is well known that only sessile lesions produce epilepsy, but no correlation has been established between the different types of sessile hamartomas and the diverse manifestations of the epilepsy. We correlate anatomic details of the hamartoma and the clinical and neurophysiologic manifestations of the associated epilepsy. METHODS: HHs of seven patients with epilepsy (ages 2- 25 years) were classified as to lateralization and connection to the anteroposterior axis of the hypothalamus by using high-resolution brain magnetic resonance imaging. We correlated the anatomic classification with the clinical and neurophysiologic manifestations of the epilepsy as evaluated in long-term (24 h) video-EEG recordings. RESULTS: HHs ranged in size from 0.4 to 2.6 cc, with complete lateralization in six of seven patients. Ictal manifestations showed good correlation with the lobar involvement of ictal/interictal EEGs. These manifestations suggest the existence of two types of cortical involvement, one associated with the temporal lobe, produced by hamartomas connected to the posterior hypothalamus (mamillary bodies), and the other associated with the frontal lobe, seen in lesions connecting to the middle hypothalamus. CONCLUSIONS: A consistent clinical and neurophysiologic pattern of either temporal or frontal lobe cortical secondary involvement was found in the patients of our series. It depends on whether the hamartoma connects to the mamillary bodies (temporal lobe cases) or whether it connects to the medial hypothalamus (frontal lobe cases).